Efficacy of lasmiditan for the acute treatment of perimenstrual migraine. (December 2022) - MacGregor, E Anne; Komori, Mika; Krege, John Henry; Baygani, Simin; Vincent, Maurice; Pavlovic, Jelena; Igarashi, Hisaka
Background: Perimenstrual migraine attacks in women with menstrual migraine is difficult to treat. This post-hoc analysis evaluated the efficacy of lasmiditan, a high affinity and selective 5-HT1F receptor agonist, for perimenstrual attacks. Methods: Patients from two randomized, double-blind, placebo-controlled clinical trials (MONONOFU and CENTURION) were instructed to treat an attack with a single dose of study medication within four hours of pain onset. After dosing, the proportion of patients who achieved freedom from migraine-related head pain, most bothersome symptom, and disability was reported at baseline up to 48 hours after dose and pooled data were evaluated. Results: A total of 303 patients (MONONOFU N = 78; CENTURION N = 225) treated perimenstrual migraine attacks with lasmiditan 50 mg (N = 24), 100 mg (N = 90), 200 mg (N = 110), and placebo (N = 79). More patients achieved migraine-related head pain freedom with lasmiditan 200 mg versus placebo at all time points assessed. At 2 hours, 33.6% of patients in the 200-mg group (p < 0.001), and 16.7% of patients in the 100-mg (p = 0.11) and 50-mg (p = 0.19) groups were pain free, compared with 7.6% in the placebo group. Conclusions: Lasmiditan treatment of perimenstrual migraine attacks was associated with freedom from migraine-related head pain at two hours, early onset of efficacy, and sustained efficacy. Clinical Trial registration: NCT03962738 and NCT03670810